(3EQTGO GdCPgGf Edi CMcGe GdEjeGfs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO Jbj Hf edG eMeO eTgOGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B.. (3aEf Gddg JYGdi ceG ChLH Ydi GdhdO WGYI CHhjg cPdc ChLH YdjgeG GdTabI Ydjg HEHdGZ eQGOGJg aj GdWGYGJ hJMUjd EQHg ef GdbQHGJ hdeG cKQ WdH GdhdO GdYRjR eMeO (B.. (3dJUfja cJGH jMJhj Ydi GdfcJI GdHOjYI aj eSGFd GdTQjYI (B...s
(3BNQgG (B:s
... (3heY JYOO GdLfGjGJ JJYOO GdOjGJ hEf GJMO GdLGfj adh SQJ LfGjGJg Ch bJd bHd GdGfOeGd JOGNdJ GdKGfj agPG NdGUI eG CaOfG aj gPG GdcJGH hef CQGO GdJWhjd (B.. (3aYdjg HcJGHfG GdeSei HefJgi GdWdHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B2/ 227s
(3EjVGM Gdecfhf (B1\ 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis